Difference Between Male and FemDifference Between Male and Female Motorcyclist-Injury Severity: Accommodating Unobserved Heterogeneity in the Dataale Motorcyclist-Injury Severities: Accommodating Unobserved Heterogeneity in the Data: Difference Between Male and Female Motorcyclist-Injury Severities - Se, Chamroeun; Wisutwattanasak, Panuwat; Champahom, Thanapong; Jomnonkwao, Sajjakaj; รัตนวราห วัฒนวงศ์ (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 28, 2023)
In Thailand, the frequency of crashes and mortality rates are significantly higher for male motorcyclists than for their female counterparts. This study aims to investigate the effect of various associated risk factors on motorcyclist-injury outcome separated by gender. Using motorcycle-crash data in Thailand from 2016 to 2019, random parameter binary probit with heterogeneity in mean and variances was employed to explore the effects of a wide range of risk characteristics on severity of different motorcyclist gender. In the male model, significant factors are improper overtaking, riding under influence, inner-lane crashes, four-lane crashes, crashes on road with no median, flush median, depressed median, and barrier median, crashes within public area, crashes on wet road, nighttime crashes on lit or unlit road, non-rush hour crashes, evening crashes, weekend crashes, and single-motorcycle crashes. In the female model, significant factors are fatigued rider, three-leg intersection, and midnight/early morning crashes). However, some factors generated contradicting effect between male and female such as hitting a sudden crossing object, U-turn crashes, and hitting passenger car. The split in model estimation between gender is particularly important that could potentially assist policymaker, safety professionals, practitioners, trainer, government agency or highway designer in future planning and serves as guidance for mitigation policies directed at safety improvement for motorcyclist.